Hematopoietic Stem Cell Transplantation in the Management of Myelodysplastic Syndrome: A Retrospective, Current, and Future Perspective - Qimudesiren; Wenjie Yin; Yuhong Wang; Guo Qing; Jinhua Bao; Chaomurilige; Shana Chen; Liren Qian (Cell Transplantation)
Myelodysplastic syndrome (MDS) is a clonal disorder that affects hematopoietic stem cells (HSCs), primarily occurring in the elderly population. Lower-risk MDS is characterized by a decrease in blood cells, whereas higher-risk MDS is associated with an increased risk of transformation to acute myeloid leukemia (AML). Currently, the treatment of MDS is still unsatisfactory, although demethylating agents, azacitidine (AZA), and decitabine (Dec) have been successfully used to treat MDS and improve survival rates. However, hematopoietic stem cell transplantation (HSCT) remains the only curative treatment for MDS patients, effectively increasing patient survival and quality of life. Nevertheless, treatment-related toxicity, graft-versus-host disease, infectious complications, and relapse are still major post-transplant issues. In this review, through a retrospective analysis of past and present HSCT for the treatment of MDS, we provide insights for the future.